The Representation of Culture in English Textbooks Prescribed for High Schools in Indonesia - Arnis Silvia (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2015)
This study investigated the culture representation of two prescribed English textbooks suggested by the Indonesian Curriculum and Publishing Centre (Puskurbuk) used in high schools in Indonesia. Its aim was to investigate whether the representation of culture supported the main goal of English as a Foreign Language (EFL) teaching, which is intercultural communicative competence (ICC). For this purpose, culture was classified as source, target, and international target culture (Cortazzi & Jin, 1990). A classification on the level of ICC was also conducted to these textbooks. It was found that the prescribed English textbooks portrayed the culture of local (Indonesia), the culture of target countries (American and British), and the culture of other international countries in a quantitatively similar portion. However, qualitatively, the presented culture tended to be artificial instead of substantial. Comparison and contrast among cultures were not found, therefore, intercultural competence was not achieved.